2006
DOI: 10.1152/jn.00040.2006
|View full text |Cite
|
Sign up to set email alerts
|

Septo-Hippocampal Networks in Chronically Epileptic Rats: Potential Antiepileptic Effects of Theta Rhythm Generation

Abstract: A series of experiments was carried out testing the hypothesis that the septal region decreases the hippocampal susceptibility to hyperexcitability states through theta rhythm generation. Medial septal neurons were simultaneously recorded with hippocampal field potentials to investigate the septo-hippocampal function in the pilocarpine model of chronic epilepsy. The theta rhythm from chronically epileptic rats had lower amplitude (20% less) and higher frequency than controls (from 3.38 to 4.25 Hz), suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 39 publications
7
92
1
2
Order By: Relevance
“…A large body of literature demonstrates a substantial decrease in hippocampal theta oscillation power and a small decrease in peak theta frequency in multiple rodent models of TLE (34)(35)(36)(37)(38)(39)(40)(41)(42). In addition to loss of power, theta oscillations are less coherent within the hippocampus, with a clear loss of theta coherence demonstrated between regions receiving temporoammonic and perforant path entorhinal inputs, mainly in proximal locations (closer to CA3) (40).…”
Section: Theta Rhythmopathy In Models Of Tlementioning
confidence: 99%
“…A large body of literature demonstrates a substantial decrease in hippocampal theta oscillation power and a small decrease in peak theta frequency in multiple rodent models of TLE (34)(35)(36)(37)(38)(39)(40)(41)(42). In addition to loss of power, theta oscillations are less coherent within the hippocampus, with a clear loss of theta coherence demonstrated between regions receiving temporoammonic and perforant path entorhinal inputs, mainly in proximal locations (closer to CA3) (40).…”
Section: Theta Rhythmopathy In Models Of Tlementioning
confidence: 99%
“…A potential explanation comes from animal studies demonstrating that septal cholinergic neurons are resistant to seizure-induced neuronal loss 8,17 and may actually enlarge in TLE via a mechanism dependent upon nerve growth factor (NGF) released from hippocampus and transported to septal nuclei retrogradely along the fornix. 18,19 NGF is an essential growth factor for septal cholinergic neurons, and its production is highly upregulated by hippocampal seizures.…”
Section: 2mentioning
confidence: 99%
“…2,3 In animal models of temporal lobe epilepsy (TLE), medial septal lesions facilitate epileptogenesis, and chemical or electrical septal stimulation can stop and prevent seizures. [4][5][6][7][8] To our knowledge, no studies have examined septal nuclei structure in human TLE.…”
mentioning
confidence: 99%
“…It is possible that the increase in the number of neurons operating in the rhythmic mode in the MSDB of the epileptic brain is of adaptive significance; thus, it was shown that theta-oscillations fulfill the protective function in the animals with the models of TLE (Miller et al 1994;Ferencz et al 2001;Colom et al 2006;Kitchigina and Butuzova 2009). The results of the study give a deeper insight into the mechanisms of epileptogenesis and contribute to the development of new approaches to the treatment of TLE.…”
Section: Functional Changes Of the Gabaergic System Of Msdb In The Epmentioning
confidence: 81%